Locomotor adaptations in the Early Miocene species Diamantomys luederitzi (Rodentia, Mammalia) from Uganda (Napak). (14th February 2023) - Bento Da Costa, Laura; Bardin, Jérémie; Senut, Brigitte
Abstract: The study of morphological adaptations to different ecological parameters among fossil vertebrates has been an important challenge in recent decades. In this paper, we focus on the link between morphological traits and locomotor behavior such as terrestriality, fossoriality and arboreality (including gliding). One of the most diverse groups in which various locomotor habits are represented is rodents, occupying a wide range of ecological niches. This work highlights morphological variations in skulls and humerus in extant rodents with varying locomotion, to predict this parameter in the extinct species Diamantomys luederitzi (Early Miocene, Napak, Uganda). Linear discriminant analysis and phylogenetic flexible discriminant analysis are used to analyze datasets obtained via traditional morphometry (measurements) and geometric morphometrics (landmarks). The results show good discrimination between locomotor groups for both structures in extant species: the skull has a wider and longer rostrum in terrestrial and fossorial taxa compared to arboreal rodents, is also higher and posteriorly wider in fossorial taxa; the distal humerus shows elongation of the trochlea and capitulum and a higher trochlea in fossorial and terrestrial species, allowing an increase of stability instead of mobility, which is more important in arboreal taxa for movement in trees. In D. luederitzi, all skull analyses except one predicted it as a terrestrial species, the other prediction as a glider was possibly linked to the diet. For the distal humerus, this species has been predicted as a terrestrial, fossorial and arboreal taxon in differing analyses, reflected by morphological traits represented in these different locomotor categories. These varying predictions could highlight the intraspecific variation in this fossil species as well as its locomotor repertoire, raising a discussion about the use of different methods in such analyses. In addition to these predictions, several issues are discussed, such as the presence of locomotor signal in the skull and its validity in locomotor studies, as well as the relevance of the use of fragmentary material in such analyses. The results obtained in this work highlight the importance of the locomotor signal in these structures, as well as the possibility of taking into account poorly preserved material, in particular the distal humerus. Abstract : This work highlights morphological variations in skulls and humerus in extant rodents with varying locomotion, to predict this parameter in the extinct species Diamantomys luederitzi (Early Miocene, Napak, Uganda). The use of LDA and phylogenetic flexible discriminant analyses with different data sets (measurements and landmarks) allow a better understanding of the locomotor repertoire of the Early Miocene species, predicted as a generalist.